Infected epidermal cyst of the clitoris in an infant - M. Doan; A. de Buys Roessingh; E. Tenisch; O. El Ezzi (Elsevier, 2021)
Clitoral enlargement in the pediatric population is a rare condition, usually related to problems of sexual differentiation, but malignant and benign clitoral lesions have also been described. We report the case of a newborn infant, investigated at birth for an intersex disorder because of clitoromegaly. Hormonal screening was normal and ultrasound (US) did not show a pelvic or abdominal mass. Three weeks later, the lesion was larger, tense and erythematous. An abscess was suspected. A drainage was then performed, and the bacteriological culture revealed the presence of Staphylococci aurei. A magnetic resonance imaging (MRI) performed to exclude a tumor of the soft tissue was normal. A diagnosis of infected epidermal cyst was confirmed by the pathology. Two months later, the external genital aspect was normal and the child asymptomatic.